Ganti Nama di Kalangan Keturunan Tionghoa Peraturan dan Kebebasan - Sutanto, Irzanti (Wacana, Journal of the Humanities of Indonesia, 2002)
In 1966 New Order regime imposed a regulation that demands Indonesian citizens of Chinese descendants to change their name with "Indonesian name" to accelerate the process of assimilation "foreign descendents" into Indonesian society. This article examines this practice of changing names by surveying the name of Chinese in the obituary section of mass media. The writer argues that the regulation allows the Chinese descendants to change their names in any way they find appropriate. In doing to, it expands the anthrophoneme deixis function in Indonesia.